Final answer:
To solve for c in the equation 2abc + d = 3, subtract d from both sides and then divide by 2ab, yielding the solution c = (3 - d) / (2ab).
Step-by-step explanation:
To solve for c in the equation 2abc + d = 3, we must isolate c on one side of the equation. Here's how we can do it:
- Subtract d from both sides of the equation to get 2abc = 3 - d.
- Divide both sides of the equation by 2ab to get c = (3 - d) / (2ab)
The correct solution for c using these steps is c = (3 - d) / (2ab). This matches with option 1 and 3 provided in the question, assuming the options are meant to represent fractions correctly, and the correct expression should have parentheses around 3 - d.